Offer and acceptance as a way of realising free will in civil law - Savchenko, VO (Interregional Academy of Personnel Management / Міжрегіональна Академія управління персоналом, 2023)

(untitled)
The article’s purpose: define offer and acceptance as a way of realising free will in civil law. Research methods: general scientific methods: logical (deduction and induction, analysis and synthesis, abstraction and comparison) and hermeneutic (for understanding scientific texts); special scientific methods: formal-dogmatic and comparative-legal. Results: The dispositive nature of civil law determines the specifics and rules of relevant legal relations, which are based on free expression of will, principles of justice and freedom of contract. Understanding the ways and forms by which participants in legal concerns express their will to create rights and obligations is of fundamental importance for all sub-branches and institutions of civil law. One of the critical ways to exercise freedom of will in civil law is an offer and acceptance as the basis for the emergence of contractual legal relations. The study paid attention to the legal understanding of the offer and acceptance, as a result of which it was proved that they are a way of exercising the freedom of will of the participants in the legal relationship. It is emphasised that the offer and acceptance are legitimate when they comply with the principles of contract law, namely the principle of freedom of contract and good faith, because they are crucial at the stage of concluding the contract. It is noted that the offer and acceptance are based on free will, as the ability to make and implement decisions. Attention is also paid to the meaning of the offer and acceptance at various stages of the contractual relationship. As a result, it was concluded that the offer and acceptance become a form of expression of free will at the scene when the parties determine the terms of the contract and complete it. Conclusions: 1) the contract is an agreement of the parties’ free will and requires a combination of internal will (desire, interest) and expression of will in the form of an offer and acceptance. Only when the will and the expression of will coincide can the contract be valid; 2) when the parties harmonise the terms of the contract (offer) and conclude it (acceptance), the consensus is reached; 3) offer and acceptance are the legal form of a promise. Thus, the offeror expresses his free will through an offer to conclude a contract and the acceptor through its acceptance. That is, the parties promise each other that they will undertake specific duties that they will perform adequately; 4) the freedom of will of the parties is agreed upon at the stage of defining the terms of the contract and its conclusion because the acceptance and offer reflect and confirm the desire of the parties to enter into legal relations on the terms determined by them; 5) the basis of the request and acceptance is the implementation of the principles of freedom of contract and good faith because they are of crucial importance at the stage of concluding the contract; 6) contracts with defects of will are recognised as invalid because when concluding a contract under the influence of deception or coercion, the counterparty’s will is negatively affected, does not express his wishes and does not correspond to his interests. In this case, the offer and acceptance do not comply with the principle of voluntariness. Мета статті полягає у визначенні оферти та акцепту як способів реалізації свободи волі в цивільному праві. Методи дослідження: загальнонаукові методи: логічний (дедукції та індукції, аналізу й синтезу, абстрагування і порівняння) та герменевтичний (щодо розуміння наукових текстів); спеціально-наукові методи: формально-догматичний та порівняльно-правовий. Результати дослідження: Диспозитивність цивільного права обумовлює специфіку та правила існування відповідних правовідносин, які ґрунтуються на вільному волевиявленні, принципах справедливості та свободи договору. Принципове значення для всіх підгалузей та інститутів цивільного права має розуміння способів та форм, за якими учасники правовідносин виявляють власну волю, направлену на створення прав та обов’язків. Одним з ключових способів реалізації свободи волі в цивільному праві є оферта та акцепт, як базис для виникнення договірних правовідносин. В дослідженні приділено увагу правовому розумінню оферти та акцепту, в результаті чого доведено, що вони є способом реалізації свободи волі учасників правовідносин. Наголошено, що оферта та акцепт є правомірними коли відповідають принципам договірного права, а саме принципу свободи договору та добросовісності, адже саме вони мають ключове значення на етапі укладання договору. Зазначено, що оферта та акцепт ґрунтуються на свободі волі, як можливості приймати та реалізовувати рішення. Також приділена увага значенню оферти та акцепту на різних етапах договірних правовідносин. В результаті цього зроблено висновок, що оферта і акцепт стають формою виразу свободи волі на етапі коли сторони визначають умови договору та укладають його. Висновки:1) договір є узгодженням свободи волі сторін та потребує поєднання внутрішньої волі (бажання, інтерес) та волевиявлення у формі оферти та акцепту. Договір може бути дійсним лише коли воля та волевиявлення співпадають; 2) коли сторони визначають умови договору (оферта) та укладають його (акцепт) відбувається здобуття консенсусу; 3) оферта та акцепт є правовою формою обіцянки. Оферент виражає власну свободу волі через пропозицію укласти договір, а акцептант, через її прийняття. Тобто, сторони обіцяють один одному, що візьмуть на себе певні обов’язки, які будуть виконувати належним чином; 4) свобода волі сторін узгоджується на етапі визначення умов договору та його укладання, адже акцепт та оферта відображають та підтверджують бажання сторін вступити у правовідносини на визначених ними умовах; 5) в основі оферти та акцепту знаходиться реалізація принципів свободи договору та добросовісності, адже саме вони мають ключове значення на етапі укладання правочину; 6) договори з вадами волі визнаються недійсними через те, що при укладанні договору в результаті омани або примусу воля контрагента зазнає негативного впливу, не виражає його бажання та не відповідає його інтересам. В цьому випадку оферта та акцепт не відповідають принципу добровільності.